Dampak Globalisasi Terhadap Perekonomian Negara Berkembang - Eka Gaetri Utari; Rina Stiani; Qoniatul Hasanah; Gustina Masitoh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Using an econometric approach, this study attempts to assess and quantify how globalisation has affected the economy of developing nations. By boosting cross-border information flows, foreign investment, and international trade, globalisation has become a major force in changing the structure of the world economy. Its consequences on social inequality, wealth distribution, and economic stability are still complicated, particularly for emerging countries. This study examines how the Human Development Index (HDI), a measure of economic welfare, is related to the economic aspects of globalisation, including capital flows, technology, and international monetary policy. Finding correlations between globalisation variables and macroeconomic indicators in developing nations is done quantitatively using econometric methods, and both descriptive and inferential analyses are carried out to give a thorough picture of how globalisation has affected important economic sectors. influence on important economic sectors. According to research, globalisation has two opposing effects: on the one hand, it increases economic growth and efficiency through trade and technical development, while on the other, it makes inequality and reliance on international markets worse. These understandings are essential for creating egalitarian and flexible economic policies that can improve living standards in emerging nations. Additionally, the report suggests national policies to improve domestic sectors and promote sustainable human development in order to lessen the negative consequences of globalisation.